ANALISIS JUAL-BELI EMAS SECARA TIDAK TUNAI: TELAAH KRITIS FATWA DSN-MUI NOMOR: 77/DSN-MUI/V/2010 - Nurul Sri Ramadhani; Rafi’ah Indah Syahrani (Al Qadhi, 2023)
Based on Islamic economic principles, the purpose of this study is to evaluate non-cash gold purchase transactions. The examination technique utilized is subjective unmistakable exploration using a writing survey approach. An inductive method was used to analyze the data. The discoveries show that non-cash exchanges in gold buys don't line up with Sharia standards in Islamic financial aspects. In view of Sharia texts managing exchanges including wares like gold, there is no unequivocal preclusion referenced, making it trying to reach direct determinations. Be that as it may, a legitimate condition in gold exchanges requires the synchronous trade of merchandise in a solitary social occasion. According to Islamic economic principles, therefore, the transaction would be deemed invalid if the parties have separated and the exchange of goods has not occurred simultaneously in a single meeting.